2018
DOI: 10.3389/fmicb.2018.01944
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate in Lactobacillus and Its Link to Stress Tolerance and Probiotic Properties

Abstract: The synthesis of the inorganic polymer polyphosphate (poly-P) in bacteria has been linked to stress survival and to the capacity of some strains to sequester heavy metals. In addition, synthesis of poly-P by certain strains of probiotic lactobacilli has been evidenced as a probiotic mechanism due to the homeostatic properties of this compound at the intestinal epithelium. We analyzed the link between poly-P synthesis, stress response, and mercury toxicity/accumulation by comparing wild-type strains of Lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…reuteri against HOCl anaerobically, and more work will be needed to understand the mechanism underlying this effect. PolyP plays a role in stress resistance and probiotic phenotypes in several different Lactobacillus species (8590). In E.…”
Section: Resultsmentioning
confidence: 99%
“…reuteri against HOCl anaerobically, and more work will be needed to understand the mechanism underlying this effect. PolyP plays a role in stress resistance and probiotic phenotypes in several different Lactobacillus species (8590). In E.…”
Section: Resultsmentioning
confidence: 99%
“…), an increased synthesis of inorganic polymer polyphosphate, the role of Poly‐P as a molecule that modulates host‐signalling pathways (Alcántara et al . ) or the addition of poly‐Ƴ glutamic acid (Bhat et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus plantarum WCFS1 (Siezen et al, 2012), L. plantarum Lpp+ (Alcántara et al, 2018) and derived mutants were grown in MRS medium at 30 °C under static conditions. Escherichia coli DH10B was used as a cloning host and it was grown in LB medium at 37 °C under aeration.…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
“…However, it has not been clearly determined which cell components are involved in Hg binding. Polyphosphate, an efficient metal chelator, is produced by numerous species of lactobacilli (Alcántara et al, 2014) but has been shown to have no effect in Hg binding (Alcántara et al, 2018). Previous results suggested that Hg mainly bound the cell envelope of Lactobacillus cells (Alcántara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%